Gig Economy Management: Strategies for Managing a Flexible Workforce in the Digital Ecosystem - Maulid Sakaria (Oikonomia : Journal of Management Economics and Accounting, 2026)
The rapid expansion of the gig economy has fundamentally transformed the nature of work, challenging traditional paradigms of human resource management (HRM) and organizational control. This article examines management strategies for flexible workforces operating within digital ecosystems, with particular emphasis on algorithmic management, digital platform dynamics, and their implications for worker autonomy, engagement, and performance. Drawing on a systematic review of peer-reviewed literature published between 2021 and 2025, this study synthesizes evidence from multiple disciplines including HRM, organizational behavior, information systems, and labor economics. The analysis identifies eight major thematic clusters, including algorithmic management, digital HRM, worker autonomy, recruitment processes, job crafting, regulation, socio-technical dynamics, and sector-specific findings. Results reveal that algorithmic control pervades gig work, creating tension between operational efficiency and worker well-being. Platform-mediated HRM replaces conventional managerial functions with data-driven mechanisms, raising critical questions about fairness, transparency, and worker representation. This article concludes with strategic recommendations for organizations, policymakers, and researchers seeking to navigate the complex landscape of gig workforce management in the digital age.